Underground Leachate Distribution Based on Electrical Resistivity in Piyungan Landfill, Bantul - Harjito Harjito; Suntoro Suntoro; Totok Gunawan; M. Maskuri (Indonesian Journal of Geography, 2018)
Piyungan Landfill is constructed to accommodate the disposal of wastes from Yogyakarta City, Sleman Regency, and Bantul Regency. Overland flow that passes through landfillsand potentially dissolves organic and anorganic materials in a high concentration is referred to as leachate. Leachate is easily transported by overland flow. It can seep through soil or land surface and, then, infiltrate into groundwater, which is commonly accessed through residential wells. Therefore, a study on leachate distribution pattern from landfill to the surrounding area becomes necessary particularly due to the potential of leachate to contaminate the environment via groundwater whose characters are latent and difficult to monitor. This research aims to (1) identify areas that experience groundwater pollution caused by leachate movement, (2) identify the distribution of electrical resistivity in polluted areas as well as the spread direction of leachateto the surrounding area, and (3) to develop a leachate management model. This research uses Electrical Resistivity Tomography (ERT) survey in order to identify the distribution of electrical resistivity in polluted areas. Groundwater quality analysis is used for validating the interpretation of ERT survey. The spread direction of leachate is identified from stratigraphic Fance model correlated with geologic and hydrologic data. The results show that groundwater contamination has occurred in the research area, as indicated by very low electrical resistivity in aquifer zone, i.e. 3-9 Ωm. Such low electrical resistivity is caused byincreased ions in groundwater as the results of leachate migrating downward into groundwater. The increased ions will trigger an increase in electrical conductivity (EC), i.e. up to 1,284 μmhos/cm, and a decline in electrical resistivity. The leachate spreads westward and northward at a depth of 6-17 m (aquifer) with a thickness of pollution between 4-11 m. The recommended landfill management model, emphasizing on leachate movement, include base lining (liner), leachate collection channel, geomembrane cap, and leachate treatment.